Analisis Kepuasan Pelanggan Berdasarkan Dimensi Servqual Menggunakan Metode Importance Performance Analysis: Studi Pada Indihome Witel Bandung - Irma Mardiana; R. Nurafni Rubiyanti (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2017)
PT. Telkom is the largest telecommunications company in Indonesia that plays an important role in the development of the national telecommunications. In 2012, PT Telkom launched IndiHome (Indonesia Digital Home), that is is a multi product bundling packages of Telkom consisting landlines, internet and interactive television services (USee Tv). As the largest telecommunications company in Indonesia, PT. Telkom should provides satisfaction through good quality services in accordance with expected by the customer.The purpose of this study is to know how satisfied customers IndiHome Witel Bandung by comparing the level of customer expectations and IndiHome Witel Bandung’s performance levels-based method SERVQUAL. Data collection method is done by distributing questionnaires to 100 customers of IndiHome Witel Bandung that currently active subscription (existing). The results of data from questionnaires, processed by using Gap analysis to know the level of customer satisfaction, after that reprocessed by using Important Performance Analysis (IPA) or also called Kartesius Diagram analysis to know which attributes or dimensions that need to be a priority IndiHome Witel Bandung for improved performance levels and any attributes or dimensions that need to be retained by the company. Based on the results of data processing, it is known customer’s appraisal on 21 of performance attributes and 21 of expectations attributes indicate that all the attributes or dimensions have a gap between customers' perception of indihome’s performance and customer expectations. As well as with the level of conformity obtained is still below 100%, ie 79.5%. It means that Indihome’s performance still has not filled customer expectations. Based on the Kartesius diagram on Important Performance Analysis (IPA), there are eight indicators and two dimensions, they are reliability dimensions and responsiveness dimensions that Indihome should be the focus to be immediately rectified their performance.